Comparative clinical characteristics of the use of digital and analog impressions on the quality of indirect restorations in patients with defects of the hard tissues of chewing teeth at different follow-up periods - Kutsyuk А. (Actual Dentistry, 2024)
Introduction. Diseases of the hard tissues of the teeth are recognized as one of the most common dental diseases. These are mainly dental caries, congenital defects, fractures, fluorosis or acid erosion. Production of indirect restorations, which require taking impressions of the jaws, is one of the most common methods of restoring the hard tissues of the tooth when they are significantly destroyed. In today’s era of growing interest in digital dentistry, researchers are still undecided whether a digital impression provides the same accuracy as a conventional impression for making indirect restorations. Goal. To conduct a comparative characterization of the use of digital and analog impressions on the quality of indirect restorations in patients with defects of the hard tissues of chewing teeth at different follow-up periods. Research materials and methods. The research involved 58 patients aged 25–60 years who applied to the Department of Stomatology of the P. L. Shupyk National Healthcare University of Ukraine for the purpose of orthopedic treatment of 79 defects of the hard tissues of the lateral teeth with destruction of 50–60% of their occlusal surface. In the course of orthopedic rehabilitation, patients were made indirect restorations — ceramic inlays using E. MAX Press material (Ivoclar Vivadent, Liechtenstein, Germany). The research group was further divided into 2 subgroups depending on the method of obtaining the impression. Subgroup A included patients who underwent digital scanning of a one-stage two-phase silicone impression, and subgroup B included patients who underwent impression removal using an intraoral digital impression system (TRIOS®, 3shape). The degree of destruction of the occlusal surface of chewing teeth and the choice of indirect restoration was carried out using the index of destruction of the occlusal surface of chewing teeth for I and II class according to Black (IROPZ). The clinical quality of indirect restorations was evaluated 1 week after the installation of the restoration and at long-term periods (12, 24, 36 months) using visual-instrumental control and according to the recommendations of the revised FDI criteria for the evaluation of direct and indirect dental restorations (2023). The presence of inflammatory changes in periodontal tissues was determined using the gingivitis index, the presence of dental plaque was determined using the OHI-S index (Green-Vermillion, 1964), the gingival sulcus bleeding index (SVI) was determined according to the Miihlemann and Son method before indirect restorations, during 1 week, 12 months and 24 month visits after cementation. Conclusion. Dental restorations made using digital impressions showed similar marginal discrepancy as restorations made using traditional impression methods (p>0.05). Lateral masticatory restorations fabricated by intraoral scanning using CAD/CAM technology have acceptable results in terms of periodontal tissue condition, color, contour, marginal adaptation, and occlusion. Although both direct and indirect digitization have been shown to be equally effective, digital impressions have shown advantages in patient acceptance of the procedure. They take less time for both the doctor and the patient and facilitate the digital workflow. No significant difference was found between conventional and digital displays in the accuracy of the 3D data sets.